MANAGEMENT OF SUFI CHARACTER EDUCATION OF SHEIKH ABDUL QADIR AL-JAILANI IN THE PERSPECTIVE OF ISLAMIC EDUCATION MANAGEMENT - Khailani Khumairoh; Husna Nashihin; Sima Farikha Syarif; Fatikhatul Muawanah (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This literature study examines the management of character education implemented by Sheikh Abdul Qadir Al-Jailani from the perspective of Islamic education management, as well as its relevance to the implementation of the Independent Curriculum based on deep learning. This study uses a qualitative approach through an in-depth literature study of the main works of Sheikh Abdul Qadir Al-Jailani and literature discussing Islamic education, Sufism, and education management. The results of the study indicate that character education developed by Sheikh Abdul Qadir Al-Jailani is structured in four components of education management: planning based on tauhid and tazkiyatun nafs; organizing learning communities through science and dhikr assemblies; implementing learning that includes cognitive, affective, and psychomotor dimensions; and supervision carried out spiritually through muhasabah and spiritual guidance. This concept is in line with the principle of deep learning in the Independent Curriculum which emphasizes character development, reflective interpretation of material, habituation of noble values, and student learning independence. The implications of this study show the importance of integration between Sufi values ​​in Islamic education management with an in-depth learning approach in the Independent Curriculum, so that the formation of students' characters becomes more complete, has high reasoning power, and has noble morals according to the demands of the digital era.